Accident At Work - A Real Challenge for Polish Companies - Katarzyna BOCZKOWSKA; Konrad NIZIOLEK (Communications of International Proceedings, 2021)
The management of OHS area still is not effective in polish enterprises, which is unfortunately confirmed by the high accidents statistics. Paper presents the study results from the complete accident documentations coming from 225 accidents at work. We proved that selected sample is not significantly different from the distribution of the general population taking into consideration the causes of the accidents at work in Poland. The most common irregularity in the post-accident procedure is the lack of defining the causes of work accident. Our detailed research has shown that most often an accident is caused by human error, especially Insufficient concentration on the executed activity (45%) and surprise of an unexpected event (52%). This definition of the causes which is too general, laconic cannot lead to a creation of effective repair plans and preventive plans. Therefore it is necessary to look for the indirect causes which can use the more advanced methods. Unfortunately, despite the availability of many techniques and tools of modeling accidents, the workers of OHS services do not use it (there are to difficult, complex), then the proposed activities and recommendations after the accident are often accidental. In our opinion simple TQM tools (Ishikawa diagram and WHY-WHY?) could be use in accident at work investigation, thus the indicated reasons will be more accurate and preventive measures will be more affective.
Keywords: Accidents at Work; Accident Investigation; Causes of Accident